The Phase Space Formulation of Time-Symmetric Quantum Mechanics - Charlyne de Gosson; Maurice A. de Gosson (Quanta)
Time-symmetric quantum mechanics can be described in the Weyl–Wigner–Moyal phase space formalism by using the properties of the cross-terms appearing in the Wigner distribution of a sum of states. These properties show the appearance of a strongly oscillating interference between the pre-selected and post-selected states. It is interesting to note that the knowledge of this interference term is sufficient to reconstruct both states.